Enhancing Learners’ Engagement and Performance in Learning through E-Resources and Services: National Open University of Nigeria Students as Beneficiaries - Ofodu, Patricia Ngozi; Ekwueme, Loveth Ogoegbunam (West African Journal of Open and Flexible Learning, 2024)
Enhancement of performance on learning among learners has been on the increase due to digital information and technologies provided by libraries, because of its backbone in academic pursuit. This study investigates enhancing learners’ engagement and performance in learning through e-resources and services. The study was guided by four research questions with two hypotheses, which examined the availability of e-resources, the frequency of usage, the influence of usage and the factor undermining the usage of electronic resources. The findings from the study revealed that there are some e-resources available for the users’; there are users that are making use of the electronic resources occasionally and daily, while some don’t use e-resources at all. The study also revealed that the use of electronic resources influenced the users’ class tests, assignments, seminar presentations and more, while there was also evidence of non-assistance from the use of e-resources in some students’ learning pursuits. The study equally revealed some of the factors undermining the use of e-resources including inadequate power supply, poor internet connectivity, lack of technology competence and limited access to computer terminals, etc.Résumé : L’amélioration des performances d’apprentissage chez les apprenants a en raison de l’information numérique et des technologies fournies par les bibliothèques, en raison de leur épine dorsale dans la poursuite académique. Cette étude porte sur l’amélioration de l’engagement et de la performance des apprenants dans l’apprentissage grâce aux ressources et aux services électroniques. L’étude a été guidée par quatre questions de recherche reposant sur deux hypothèses, qui ont examiné la disponibilité des ressources électroniques, la fréquence d’utilisation, l’influence de l’utilisation et le facteur qui nuit à l’utilisation des ressources électroniques. Les résultats de l’étude ont révélé qu’il existe des ressources électroniques disponibles pour les utilisateurs ; Certains utilisateurs utilisent les ressources électroniques de temps en temps et quotidiennement, tandis que d’autres n’utilisent pas du tout les ressources électroniques. L’étude a également révélé que l’utilisation des ressources électroniques avait une influence sur l’examen de classe, le devoir, la présentation du séminaire et plus encore, tandis qu’il y avait également des preuves de non-assistance de l’utilisation des ressources électroniques dans la poursuite de l’apprentissage de certains étudiants. L’étude a également révélé certains des facteurs qui entravent l’utilisation des ressources électroniques, notamment l’approvisionnement en électricité inadéquat, la mauvaise connectivité Internet, le manque de compétences technologiques et l’accès limité aux terminaux informatiques, etc.Mots-clés : Amélioration, engagement des apprenants, performance d’apprentissage, ressources électroniques et services
Keywords: Enhancing; learners’ engagement; learning performance; e-resources and services